Access and Usage Patterns of Mobile Phones, Internet and Video Games in Venezuelan Youth: Challenges for Training in Cyberculture - Henríquez Coronel, Patricia; Arellano, Germán Antonio; Henríquez, María Angélica; Bello, María Eugenia (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2013)
This article presents partial results of a study whose has been financing with public funds in Venezuela. The main purpose has been describing the use of cell phones, Internet and videogames in young people in San Cristobal City. The description included two areas: a) Access and usage patterns about Internet, cell phones and videogames b) Infor-mation process habits on Internet in relation with school knowledge.In the first phase of the research project, a ques-tionnairehad been designed. Itwas applied to 214 students between 12 and 17 years old.The students belonged to three different types of schools in the city: nonprofit schools, private schools and religious school. The data had been proces-sed with descriptive statistic measures. The results shown below belong to one of the three schools picked out. The basic equipment for the young people surveyed is a computer, a printer, a tv cable and internet connection. The scope of the cell phonestechnology is the biggest with88% of them. The use of videogames is less than the use of internet and cell phones. Cell phone technology is essential, almost never goes out and keeps them in touch with parents and friends. Internet is an essential source for information for schoolwork but above a space for socializing and entertainment, repre-sents a new way of "being". Video games are despite their lower employment compared to the other two technologies a primary form of entertainment and youth group interaction. Generally young people surveyed are youngsolitary media-tion regarding adult but with a high peer contact.